1975
DOI: 10.1111/j.1432-1033.1975.tb02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase of Bacteriophage T7

Abstract: Protein kinase, which was isolated from cells infected with T7, is indeed a viral gene product. This is shown by DNA‐dependent synthesis in vitro. The protein kinase transfers phosphate from ATP to seryl or threonyl residues in protein. The enzyme has only a relative requirement for magnesium ions, but is only active at low ionic strength. The best substrate is lysozyme. T7 protein kinase activity is not stimulated by cyclic 3′: 5′‐AMP and/or cyclic 3′: 5′‐GMP. The T7 protein kinase carries – SH groups essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 13 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Since T7PK obtained in this manner is phosphorylated ([8] and vide infra ) it is referred to as H-pT7PK, with ‘H’ and ‘p’ referring to the His-tag and phosphate group(s), respectively. Since a previous study indicated that phosphorylation reduces T7PK catalytic activity [7], a method was developed to dephosphorylate H-pT7PK, as well as remove the His-tag, which also could affect activity. H-pT7PK was treated with lambda phage protein phosphatase [20], which has a broad specificity for protein phosphomonoester groups [21,22], then subjected to Ni 2+ -NTA affinity chromatography, providing H-T7PK in a yield of ~10%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since T7PK obtained in this manner is phosphorylated ([8] and vide infra ) it is referred to as H-pT7PK, with ‘H’ and ‘p’ referring to the His-tag and phosphate group(s), respectively. Since a previous study indicated that phosphorylation reduces T7PK catalytic activity [7], a method was developed to dephosphorylate H-pT7PK, as well as remove the His-tag, which also could affect activity. H-pT7PK was treated with lambda phage protein phosphatase [20], which has a broad specificity for protein phosphomonoester groups [21,22], then subjected to Ni 2+ -NTA affinity chromatography, providing H-T7PK in a yield of ~10%.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal domain possesses T7PK activity, while the SO activity is associated with the C-terminal region, and represses transcription by an unknown mechanism that is independent of T7PK activity [6]. T7PK uses ATP as phosphate donor and requires Mg 2+ as a cofactor [7]. The T7PK domain of the 0.7 gene has been separately cloned and the polypeptide expressed in recombinant form [8].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for and functions of local polymorphisms of the proteins are unclear, but they can be explained in part by evolution for optimal interaction with host proteins. gp0.7 is a serine/threonine protein kinase and phosphorylates translational components (IF1, IF2, IF3, elongation factor G, and ribosomal proteins S1 and S6), host RNAP ␤Ј subunit, and enzymes related to mRNA metabolism (RNase III and RNase E), resulting in exclusive phage gene expression (41,43,48,55,57,58,65,81). gp6 is an exonuclease and contributes to the packaging of concatemerized phage DNA by suppressing the packaging of host DNA (69).…”
Section: Vol 74 2008 Characterization Of a T7-like Virus (Sg-jl2) 6975mentioning
confidence: 99%
“…The enzyme has maximal activity at 6 min after infection at 37°C, after which it rapidly declines to near preinfection levels. Various T5 phage-induced functions inhibit or modify host activities (7,17,18), and a T7 phageinduced enzyme, in effect, self-destructs (13).…”
mentioning
confidence: 99%